P506 Endoscopic and clinical outcomes of upadacitinib in patients with moderate to severe Crohn's disease by baseline disease severity. (30th January 2023) - Siegmund, B; Patel, K; Torres, E A; Lakatos, P L; Seidelin, J; Fleisher, M; Ford, S; Remple, V; Lacerda, A P; Anyanwu, S; Garrison, A; Panés, J
Abstract: Background: Upadacitinib (UPA) is an oral selective Janus kinase inhibitor with demonstrated efficacy in induction and maintenance treatment of Crohn's disease (CD). This post hoc analysis assessed the efficacy of UPA in patients with CD by baseline (BL) disease severity. Methods: In the U-EXCEL (NCT03345849) and U-EXCEED (NCT03345836) induction studies, patients with moderate-to-severe CD and intolerance/inadequate response to biologic therapy (both studies) and/or conventional therapy (U-EXCEL) received UPA 45 mg once daily (QD) or placebo (PBO) for 12 weeks. Patients who achieved clinical response to UPA induction were re-randomised in a maintenance study (U-ENDURE, NCT03345823) to receive UPA 15 mg QD, UPA 30 mg QD, or PBO for 52 weeks. Clinical remission and endoscopic response were evaluated in subgroups stratified by BL disease characteristics: Crohn's Disease Activity Index (CDAI), very soft/liquid stool frequency (SF), abdominal pain score (APS), and Simple Endoscopic Score for CD (SES-CD). Patients from the U-EXCEL and U-EXCEED studies were pooled for analysis. Results: Among 1021 patients with moderate-to-severe CD (UPA 45 mg, n=674; PBO, n=347), week 12 clinical remission and endoscopic response rates were significantly higher for patients receiving UPA 45 mg vs PBO regardless of BL disease severity (nominal P <.01), except SES-CD <6 (UPA, n=35; all had ileal disease only per the inclusion criteria) (Figure 1). UPA efficacy rates were higher compared with PBO across BL CDAI, with variable treatment effects. Patients with lower BL SF achieved clinical remission and endoscopic response with UPA 30 mg at higher rates than those with higher BL SF at week 12 and week 52. At week 12, the absolute efficacy rates and treatment differences for clinical remission and endoscopic response were generally similar across BL APS. Patients with higher BL SES-CD (≥15) generally achieved higher rates of clinical remission and endoscopic response at week 12 with UPA vs PBO than those with lower BL SES-CD (6–14). At week 52, clinical remission and endoscopic response rates were generally higher for patients receiving UPA vs PBO and most were consistent with a dose-response relationship (Figure 2). Generally, larger treatment differences between UPA and PBO were observed for patients with the most severe disease per SES-CD. Conclusion: UPA induction and maintenance therapy improved clinical and endoscopic outcomes vs PBO in patients with moderate-to-severe CD, across levels of disease severity. Data for the small subgroup of patients with SES-CD <6 should be interpreted cautiously given lower mucosal healing rates in isolated ileal CD.1 Reference: 1. Atreya R, et al. Curr Res Pharmacol Drug Discov . 2022;3:100097.